Черное золото: [повесть] / Сергей Зверев - Зверев Сергей Иванович (Морской спецназ, 2007)
Экземпляры: ф.18 (ретро) / Инвентарный номер: 44432 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: З-43 / ББК: 84(2Рос=Рус)6-4